The Alberta Reconstructive Technique: An Occlusion‐Driven and Digitally Based Jaw Reconstruction. (26th June 2019) - Seikaly, Hadi; Idris, Sherif; Chuka, Richelle; Jeffery, Caroline; Dzioba, Agnieszka; Makki, Fawaz; Logan, Heather; O'Connell, Daniel A.; Harris, Jeffrey; Ansari, Kal; Biron, Vincent; Cote, David; et al.
Abstract : Objectives/Hypothesis: The free flap reconstructive protocols of the jaws have been refined over the years and presently are based on bone‐driven approaches that generally use the lower border of the mandible or the anterior surface of the maxilla as the templates for reconstruction because these contours are deemed important to the eventual cosmetic outcomes of patients. The ultimate goal of functional jaw reconstruction, however, is the reconstruction of the dental occlusion and oral rehabilitation. The purpose of the present study was to evaluate the Alberta reconstructive technique (ART), which is a new approach of occlusion‐driven jaw reconstruction with digitally planned immediate osseointegrated implant installation. Study Design: Prospective cohort study. Methods: This research study considers the ART's safety, effectiveness, accuracy, timeliness of reconstruction, aesthetic appeal, and cost‐effectiveness in comparison with the standard bone‐driven and delayed osseointegrated implant installation (BDD) protocol. Results: The ART procedures were as safe and more effective at achieving full occlusal reconstruction and oral rehabilitation. The ART cohort of patients achieved oral rehabilitation in 21.4 month as compared to 73.1 months for the BDD cohort. There were no differences in the aesthetic appeal the two groups. The ART cost an average of $22, 004 less than BDD and we calculated the quality adjusted life years gain to be between 2.14 and 4.04 in favour of ART. Conclusions: The ART is a good option for patients with jaw defects. It provides a safe, effective, accurate, aesthetic, and cost‐effective reconstruction that restores form and function in a timely manner. Level of Evidence: 2b Laryngoscope, 129:S1–S14, 2019